Gadget Use and Islamic Education Achievement among Elementary School Children - Meilany, Devany Rizky Fulan; Fauji, Imam (Indonesian Journal of Cultural and Community Development, 2025)
The rapid expansion of digital technology has intensified concerns regarding children’s gadget use and its implications for learning outcomes, particularly in religious education contexts. In elementary education, inappropriate gadget exposure is often associated with declining academic performance, while guided use may offer educational benefits. This study aims to examine the relationship between gadget use and learning achievement in Islamic Religious Education among elementary school children. A quantitative correlational design was employed involving 20 elementary school students aged 6–11 years. Data were collected through questionnaires measuring gadget use, academic documentation of learning achievement, parental interviews, and structured observations. Statistical analysis was conducted using Pearson product–moment correlation with the assistance of SPSS. The results reveal a statistically significant and positive relationship between gadget use and Islamic education learning achievement, indicated by a perfect correlation coefficient (r = 1.000, p < 0.05). These findings suggest that gadget use, when regulated and supervised by parents, can support cognitive development and enhance learning outcomes in religious education. The novelty of this study lies in its community-based focus, integrating home supervision, village context, and religious learning achievement rather than school-centered analysis alone. The findings contribute to the growing literature on digital technology in education by highlighting the conditional benefits of gadget use in elementary Islamic education. Practically, the study underscores the importance of parental guidance and balanced digital engagement to optimize educational outcomes, while theoretically reinforcing the role of contextual and social factors in technology-supported learning.